2023
DOI: 10.1172/jci163448
|View full text |Cite
|
Sign up to set email alerts
|

Targeting fatty acid metabolism in glioblastoma

Abstract: Glioblastoma (GBM) is a primary tumor of the brain defined by its uniform lethality and resistance to conventional therapies. There have been considerable efforts to untangle the metabolic underpinnings of this disease to find novel therapeutic avenues for treatment. An emerging focus in this field is fatty acid (FA) metabolism, which is critical for numerous diverse biological processes involved in GBM pathogenesis. These processes can be classified into four broad fates: anabolism, catabolism, regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 136 publications
1
21
1
Order By: Relevance
“…Our study raises several intriguing questions for future exploration: (1) Is the identified axis of p53 inactivation -astrocyte infiltration -FA metabolism relevant also to primary brain tumors? Glioblastomas commonly inactivate p53 (86), and have been recently shown to depend on FAS (49,(87)(88)(89)(90), suggesting that our findings may be relevant to primary brain tumors as well. ( 2) What is the exact molecular mechanism by which p53 regulates FA metabolism in the context of BCBM?…”
Section: Discussionmentioning
confidence: 75%
“…Our study raises several intriguing questions for future exploration: (1) Is the identified axis of p53 inactivation -astrocyte infiltration -FA metabolism relevant also to primary brain tumors? Glioblastomas commonly inactivate p53 (86), and have been recently shown to depend on FAS (49,(87)(88)(89)(90), suggesting that our findings may be relevant to primary brain tumors as well. ( 2) What is the exact molecular mechanism by which p53 regulates FA metabolism in the context of BCBM?…”
Section: Discussionmentioning
confidence: 75%
“…Lipid metabolism influences several processes that play a crucial role in the development and progression of GBM. Tumor-mediated reprogramming of these processes encompasses changes in import/export signaling pathways, lipid anabolism, catabolism (fatty acid oxidation), regulation of ferroptosis, and alteration in de novo lipid synthesis and signaling pathways that include lipogenesis and cholesterol synthesis and targeting these pathways may represent a potential therapeutic strategy to overcome GBM progression and disease recurrence [ 41 , 42 , 43 ]. Fatty acid metabolism has been shown to contribute to immune suppression in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, a new type of programmed cell death, has been proven to be induced by the overloading of cellular iron and ROS 36 . During the past decades of research, the regulatory factors of ferroptosis have been proposed to participate in the gliomagenesis and anti‐tumor responses 37 . In glioma cells U251 and U87, overexpression of NEDD4L significantly reinforced the cytotoxic effects induced by the natural compound paeoniflorin (PF), accompanied by inhibition of cell viability and induction of ferroptosis 38 .…”
Section: Discussionmentioning
confidence: 99%